PERMOHONAN IZIN POLIGAMI ATAS DASAR KETIDAKPUASAN PELAYANAN KEBUTUHAN SEKSUAL DITINJAU BERDASARKAN UNDANG-UNDANG PERKAWINAN (Studi Putusan Pengadilan Agama Sidoarjo Nomor 330/Pdt.G/2021/PA.Sda) - Qothrun Nada; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
Marriage is a sacred bond that is tied to one's faith and belief in Allah SWT. A marriage can not only be based on desire or only to fulfill biological needs, but in a marriage bond contains the value of worship. One form of marriage that is often discussed in Muslim society is polygamy. For example, the application for a polygamy permit based on excessive sexual needs was filed at the Sidoarjo Religious Court and the judge granted all of the requests. The problem in writing this thesis is how to apply for a polygamy permit on the basis of dissatisfaction with sexual needs services? (Study of the Decision of the Sidoarjo Religious Court Number 330/Pdt.G/2021/PA.Sda)? in this study using normative research methods using a conceptual approach, a law approach and a case approach supported by data from a literature review and also interview data to strengthen the research. Polygamy has been practiced by mankind long before Islam came. But at this time Polygamy is a legal product of Islam whose aim is to achieve the ideal of order in a particular community. Therefore, polygamy cannot be eliminated. So that when the Petitioner applied for a polygamy permit on the grounds of having excessive sexual desire it was not appropriate because based on the provisions in Law Number 1 of 1974 concerning Marriage, Islamic Law, and the Compilation of Islamic Law, it can be concluded that the obligations of a wife in a household are not just to fulfill the sexual needs of husbands who have excessive sexual desire